Effects of feeding varying ingredient particle sizes and diet forms for 25- to 50-lb nursery pigs on performance, caloric efficiency, and economics - J A De Jong; Michael D Tokach; Leland J McKinney; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 675 pigs (PIC 1050 barrows; initially 24.5 lb BW and 37 d of age) were used in a 21-d study to determine the effects of feeding varying ingredient particle sizes and diet form for 25- to 50-lb nursery pigs on performance, caloric efficiency, and economics. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 8 dietary treatments with 17 replications per treatment and 5 pigs per pen in two groups of nursery pigs. The 8 experimental diets included 3 corn-soybean meal—based diets consisting of: (1) corn fraction ground to an average of 620 Î¼ and fed in meal form, (2) corn fraction ground to an average of 352 Î¼ and fed in meal form, and (3) diet 2 but pelleted. The remaining 5 diets were high by-product diets containing 20% wheat middlings (midds) and 30% dried distillers grains with solubles (DDGS). Diets 4 to 8 consisted of: (4) corn fraction ground to an average of 620 Î¼, midds and DDGS unground from the plant with an average particle size of 534 Î¼ and 701 Î¼, respectively, and fed in meal form; (5) diet 4 but corn fraction ground to an average of 352 Î¼ and fed in meal form; (6) diet 5 but fed in pellet form; (7) corn, soybean meal, DDGS, and midds ground to average particle sizes of 352 Î¼, 421 Î¼, 377 Î¼, and 357 Î¼, respectively, fed in meal form; and (8) diet 7 but fed in pellet form. The two formulated diets were not balanced for energy, so energy was lower for treatments 4 to 8 than for treatments 1 to 3.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; DDGS; Feed processing; Nursery pig; Wheat middlings